Signal processing algorithms for multiuser MIMO relay communication systems - Khandaker, Muhammad Ruhul Amin (Curtin University, 2012)
The increasing demand for mobile applications such as streaming media, software updates, and location-based services involving group communications has prompted the need for wireless communication technologies that can support reliable high data rates. However, wireless channel is subject to signal fading that severely degrades the system spectral efficiency. By exploiting the spatial diversity, multiple-input multiple-output (MIMO) techniques can provide both theoretically attractive and technically practical solutions to combat channel fading. Moreover, in the case of long source-destination distance, single or multiple MIMO relay node(s) is necessary to combat the pathloss and/or shadowing effects of wireless channel and relay signals from the source to the destination.In this thesis, we focus on multiuser MIMO relay systems. We first present joint source, relay, and receiver optimization algorithms for the uplink system based on the minimum mean-squared error (MMSE) criterion subjecting to individual power constraints at the source and the relay nodes. The proposed algorithms outperform the existing techniques in terms of both MSE and bit-error-rate (BER). Next, in the downlink system, we consider multicasting multiple data streams among a group of users with the aid of a relay node, where all the nodes are equipped with multiple antennas. The downlink system performance is optimized subjecting to both power constraints at the source and the relay nodes and quality-of-service (QoS) constraints at the receivers.Then we present the duality between the uplink and the downlink of a multi-hop MIMO relay system. Based on this duality, we propose an optimal design of the source precoding matrix and relay amplifying matrices for multi-hop MIMO relay system with a nonlinear dirty paper coding (DPC)- based transmitter at the source node. The proposed nonlinear transmitter algorithm outperforms the existing decision feedback equalizer (DFE)-based receiver schemes.Multiuser MIMO relaying is then considered in an interference system where a group of transmitters communicate simultaneously with their desired destination nodes with the aid of multiple relay nodes, all equipped with multiple antennas. Transmit-relay-receive beamforming technique is exploited to minimize the total source and relay transmit power in conjunction with transmit power control such that a minimum QoS threshold is maintained at each receiver. The proposed scheme generalizes the existing single-hop MIMO interference systems and the single-antenna, dual-hop interference relay systems to the dual-hop interference MIMO relay systems with any number of source, relay, and destination nodes, all equipped with multiple antennas.The above algorithms are developed assuming that the instantaneous channel state information (CSI) knowledge of both the source-relay link and the relay-destination link is available at the scheduler. However, in practical relay communication systems, the instantaneous CSI is unknown, and therefore, has to be estimated. Hence, we finally propose a bandwidth efficient MIMO channel estimation algorithm that provides the destination node with full knowledge of all channel matrices involved in a dual-hop MIMO communication. The proposed approach attains smaller channel estimation error and is applicable for both one-way and two-way MIMO relay systems.